(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sugata M, Arviana N, Tampubolon L, Widjajakusuma J, Victor H, Jan TT. 2022. Identification and characterization of calcite producing bacteria isolated from soils in West Java, Indonesia. Biodiversitas 23: 3921-3927. Bio-mediated soil improvement as an interdisciplinary application of geotechnical engineering and microbiology has gained attention due to its environmentally friendly and sustainable properties. This study aimed to isolate indigenous bacteria from soils in Indonesia and evaluate their ability to precipitate calcium carbonate. Fifty-seven colonies were isolated from three soil samples of different locations in Indonesia (Cikarang, Medang, and Karawang). Screening of calcite-producing bacteria was carried out using B4 agar medium incubated for 7-14 days. Only twenty isolates showed the potential ability to form precipitate on B4 agar medium. All the twenty isolates were characterized morphologically and biochemically. For molecular analysis, two isolates, LK3 and NC7, were chosen based on the morphological similarities with Bacillus: Gram-positive, spore-forming rod bacteria. According to 16S rRNA gene sequence analysis using the Basic Local Alignment Search Tool (BLAST), LK3 was identified as Bacillus subtilis LK3 and NC7 was identified as Bacillus cereus NC7. At a temperature of 30 °C, B. cereus NC7 showed the highest growth and produced the most calcite precipitates. In addition, pH 9 was the optimum condition for crystal formation by these bacteria. In conclusion, B. cereus NC7 as indigenous bacteria might be feasible to be used for local soil improvement.